KOMBINASI ULTRASOUND DAN TRAKSI BAHU KE ARAH KAUDAL TERBUKTI SAMA EFEKTIFNYA DENGAN KOMBINASI ULTRASOUND DAN LATIHAN CODMAN PENDULUM DALAM MENURUNKAN NYERI DAN MENINGKATKAN KEMAMPUAN AKTIFITAS FUNGSIONALSENDI BAHU PADA PENDERITA SINDROMA IMPINGEMENT SUBAK - Dwi Setiyawati; Nyoman Adiputra; Muhammad Irfan (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2013)
Subacromial impingement syndrome is pain caused the emphasis of the supraspinatus muscle tendon between the acromion and the humeral tuberosity. Pain in subacromial impingement syndrome cause reduction of shoulder functional activity. Handling the problem of impingement syndrome, many modalities are heating, electrical stimulation, manual therapy and exercise therapy. This study aimed to compare result between the combination of ultrasound therapy and traction shoulder toward caudal (group 1) and combination of ultrasound therapy and Codman pendular exercise (group 2). The duration of treatment was given 3 times a week for 2 weeks long. Sampling of this research was 32 people each group of 16 people. This research was true experimental study using pre test and post test design with measurement SPADI (Shoulder Pain and Disability Index) Result of hypothesis testing using independent t-test is found p > 0.05 showed no significant differences between group 1 and group 2. Conclusions in this research that combining of ultrasound therapy and traction shoulder to caudal are proven equally effective with ultrasound therapy and codman pendular exercise to reduce pain and improve functional shoulder joint activity in patient with impingement subacromial syndrome. There for the further study it is recommended a multicentre study using three combination therapy (Ultrasound, traction and pendular exercise) for reducing pain and improving functional shoulder joint activity with impingement subacromial syndrome